DESIGN AND IMPLEMENTATION OF A DIGITAL FLIPBOOK LEARNING MODULE ON YOUTH PLEDGE TO ENHANCE CLASS XI STUDENTS’ LEARNING MOTIVATION AT SMKN 1 KASIHAN - Fitria Nungki Anjani; Muhammad Iqbal Birsyada (SOSIOEDUKASI, 2026)
Based on the researcher's experience during the implementation of School Field Introduction 2 (PLP 2), it was found that learning was not yet optimal, as teachers only used one textbook and did not use supporting media or modules. The objectives of this study are: (1) to design and develop a digital flipbook-based learning module aimed at enhancing the learning interest of Grade XI students at SMKN 1 Kasihan, and (2) to evaluate the quality of the developed module in terms of feasibility, practicality, and effectiveness. The research adopts a Research and Development (R&D) approach, employing Robert Maribe Branch’s ADDIE model, which consists of five sequential phases: Analysis, Design, Development, Implementation, and Evaluation. Data collection was conducted using two main instruments: questionnaires and written tests. The collected data were analyzed quantitatively. The findings reveal that: (1) with respect to product feasibility, the developed digital flipbook learning module has a “Very good” feasibility level with a score of “4,4”, (2) in terms of practicality, the developed digital flipbook learning module has a “very good” practicality level with a score of “4,71”, (3) in terms of effectiveness, the developed digital flipbbook learning module has an “Effective” level of effectiveness with a score percentage of “76,66%